The Identification and synthesis of metabolites of 4-(5-methyl-1,3,4-oxadiazole-2-yl)-benzenesulfonamide - Alexander L. Khokhlov; Ilya I. Yaichkov; Anton A. Shetnev; Valeria A. Panova; Julia A. Efimova; Sergey A. Ivanovskiy; Mikhail K. Korsakov; Nikita N. Volkhin; Sergey S. Petukhov (Research Results in Pharmacology)
Introduction: 4-(5-methyl-1,3,4-oxadiazole-2-yl)-benzenesulfonamide is a new selective type II carbonic anhydrase inhibitor with local action through instillation into the eyes. For a complete pharmacokinetic study of this drug, it is necessary to detect and synthesize its metabolites for their systemic exposure evaluation.